2006
DOI: 10.3732/ajb.93.9.1251
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical perspective on the role of large stem volume and high water content in baobab trees (Adansonia spp.; Bombacaceae)

Abstract: The stems of large trees serve in transport, storage, and support; however, the degree to which these roles are reflected in their morphology is not always apparent. The large, water-filled stems of baobab trees (Adansonia spp.) are generally assumed to serve a water storage function, yet recent studies indicate limited use of stored water. Through an analysis of wood structure and composition, we examined whether baobab morphology reflects biomechanical constraints rather than water storage capacity in the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 51 publications
1
55
0
5
Order By: Relevance
“…Ultimately, they are all interlinked to some degree through a continuum via plasmodesmata connections between cells within the xylem matrix and their collective link to the phloem. For instance, the mechanical role of living cells is commonly accepted to be more closely related to the RP cells, where, owing to their orientation, they increase radial strength (Beery et al, 1983; Burgert et al, 1999; Burgert and Eckstein, 2001; Reiterer et al, 2002); however, AP cells also play a mechanical role through turgor pressure (Niklas, 1992; Chapotin et al, 2006). For most woody species the fibers or ‘living’ fibers assume the mechanical role.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, they are all interlinked to some degree through a continuum via plasmodesmata connections between cells within the xylem matrix and their collective link to the phloem. For instance, the mechanical role of living cells is commonly accepted to be more closely related to the RP cells, where, owing to their orientation, they increase radial strength (Beery et al, 1983; Burgert et al, 1999; Burgert and Eckstein, 2001; Reiterer et al, 2002); however, AP cells also play a mechanical role through turgor pressure (Niklas, 1992; Chapotin et al, 2006). For most woody species the fibers or ‘living’ fibers assume the mechanical role.…”
Section: Introductionmentioning
confidence: 99%
“…It is not known if excessive water loss from parenchyma cells during drought can compromise their physiological functions, although desiccation-induced damage to the protoplasm has been documented in wood parenchyma cells during cold stress (Ristic and Ashworth 1994 ). If the maintenance of turgor pressure is important, for instance for biomechanical reasons (Chapotin et al 2006 ), increased concentration of soluble sugars could provide means for reducing the capacitive discharge from wood parenchyma cells.…”
Section: The Role Of Sapwood Nsc At the Whole Plant Levelmentioning
confidence: 99%
“…8.1b ). Last but not least, wood of some trees such as Adansonia (Chapotin et al 2006 ) or Ceiba ( Fig. 8.1f ) is extremely parenchymatous, with axial parenchyma comprising most of the matrix between vessels and rays.…”
mentioning
confidence: 99%
“…Surveys of diffuseporous angiosperms have shown that living axial and ray parenchyma tissue often constitute up to 40% or more of the total sapwood volume (Panshin and de Zeeuw 1980). In some tropical trees with low wood density and high water 4y Springer storage capacity, xylem parenchyma can occupy >75% of the total sapwood volume (Chapotin et al 2006). Thus, sapwood pressure-volume curves should reflect the volumeweighted average of the water retention characteristics of both living and dead cells.…”
Section: Coordination Of Leaf and Stem Water Relationsmentioning
confidence: 99%